Cryopreservation Protocols for Genetically Engineered Mice. Issue 5 (27th May 2021) - Longenecker, Glenn; Cho, Kyoungin; Khillan, Jaspal S.; Kulkarni, Ashok B.
Abstract: Protocols for cryopreservation of mouse embryos and sperm are important for preserving genetically engineered mice (GEMs) used in research to study human development and diseases. Embryo cryopreservation is mainly carried out using either of two protocols: controlled gradual cooling or vitrification. Sperm cryopreservation protocols include two methodologies that are commonly referred to as JAX and CARD. Quality‐control measures are necessary to ensure that GEMs are properly cryopreserved so that they can be retrieved for future use. An archiving system is also important in keeping proper records of frozen sperm and embryos. Frozen embryos and sperm are now preferred over live mice for shipping to distant locations. This article describes detailed protocols used in cryopreservation of mouse embryos and sperm, as well as their retrieval to live mice. © 2021 U.S. Government. Sperm cryopreservation Basic Protocol 1 : JAX protocol for sperm cryopreservation Support Protocol 1 : JAX protocol for making sperm cryopreservation medium Basic Protocol 2 : JAX protocol for IVF of mouse sperm Alternate Protocol 1 : Modified CARD protocol for sperm cryopreservation Support Protocol 2: CARD protocol for making sperm cryopreservation medium Alternate Protocol 2 : CARD protocol for IVF of mouse sperm Embryo cryopreservation Basic Protocol 3 : Cryopreserving and thawing 2‐cell embryos Alternate Protocol 3 : Cryopreserving and thawing 8‐cell to morula‐stage embryos Surgical transfer of embryos Basic Protocol 4 : Infundibulum transfer of 2‐cell to morula‐stage embryos